Plasma Cytokine Concentrations in Workers Exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) - Saberi Hosnijeh, Fatemeh; Boers, Daisy; Portengen, Lützen; Bueno De Mesquita, Bas; Heederik, Dick; Vermeulen, Roel (Frontiers in Oncology, 2012)
Objectives Few epidemiological studies have studied the effect of 2,3,7,8-tetrachlorodibenzo-p dioxin (TCDD) on blood cytokine levels. In this study we investigated changes in plasma levels of a large panel of cytokines, chemokines and growth factors among workers from a Dutch historical cohort occupationally exposed to chlorophenoxy herbicides and contaminants including TCDD. Methods Eighty-five workers who had been exposed to either high (n=47) or low (n=38) TCDD levels more than 30 years before serum collection were included in the current investigation. Plasma level of 16 cytokines, 10 chemokines and 6 growth factors were measured. Current plasma levels of TCDD (TCDDCurrent) were determined by high resolution gas chromatography/isotope dilution high resolution mass spectrometry. TCDD blood levels at the time of last exposure (TCDDmax) were estimated using a one-compartment first order kinetic model. Results Blood levels of most analytes had a negative association with current and estimated past maximum TCDD levels. These decreases reached formal statistical significance for fractalkine, transforming growth factor alpha (TGF-α) and fibroblast growth factor 2 (FGF2) with increasing TCDD levels. Conclusions Our study showed a general reduction in most analyte levels with the strongest effects for fractalkine, FGF2 and TGF-α. These findings suggest that TCDD exposure could suppress the immune system and that chemokine and growth factor-dependent cellular pathway changes by TCDD may play role in TCDD toxicity and associated health effects.